Investigasi Sifat Kepadatan dan Daya Dukung Bahan RAP Reclaimed Asphalt Pavement Bergradasi EME Enrobé à Module Élevé - Setyawan, Andri, Senja Rum Harnaeni, ST., MT, Ir Sri Sunarjono,MT.,Ph.D (2016)
The harden road is a facility of transportation that can be used to develop the life standard of society to access their environments including economic access and social aspect. To make technology more efficiency so has been applied recycling technology at RAP (Reclaimed Asphalt Pavement) that has been cesspool materials on the harden road. The purpose of this research is to investigate how much the solidity point and the power support of RAP with EME gradation, than being compared with the solidity point and support power of fresh aggregate with same gradation. In this research, the first step that should be done is to investigate material physical of RAP and the new aggregate to know the quality of materials that have been used. The physical investigating that has been done included the testing of mass of materials and absorbing, aeration investigation and aggregate of graduation investigation, than being done the testing of destiny with Standard Proctor test and modified Proctor EME gradation. From the test has been got the solidity point and the optimum degree of water. The next test is CBR test (California Bearing Ratio) with same gradation, CBR test is being used the optimum of degree of water based on Modified Proctor Test, from this test has been got the point of support power materials. Base on the analysis of the characteristic of solidity and the support power of RAP materials with EME gradation have shown the result that the solidity point and the support power of RAP material are lower than new aggregate. The fresh aggregate maximum of solidity at standard proctor has been 1,82 gr/cm3 with the degree of water optimum 9,80% and RAP material has been 1,49 gr/cm3 with the degree of water optimum 9,60 %, meanwhile the maximum of solidity of modified proctor has been 1,96 gr/cm3 with the degree of optimum water 9,25% and RAP material has been 1,59 gr/cm3 with the degree of optimum water 8,30%. The result of power support test by using CBR tool at fresh aggregate has been higher than RAP material, the new aggregate has been 86,67% and RAP material has been 33,33%. Base on the results of this research can be concluded that the solidity point and the support power of RAP material is lower than fresh aggregate. Keyword : recycling, CBR , EME, Proctor, RAP